2016
DOI: 10.1515/cer-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of The Ban On Uncovered sCDS Trade On The Interdependencies Between The CDS Market And Other Sectors Of Financial Markets. The Case Of Safe And Developed Versus Risky And Developing European Markets

Abstract: The aim of the article is to verify the impact of the ban on uncovered sCDS trade in Europe on the interdependencies between the sCDS market and other sectors of financial markets. We analyse two European markets: the safe and developed Swedish market, and the risky and developing Hungarian one. The study covers the period from October 2008 to October 2013. We analyse changes in the interdependencies between the sCDS market and the bond market, as well as between the sCDS market and the stock exchange.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The others were sovereign bonds and the stock exchange markets. This study extends the research by Kliber (2016) who analysed changes in the dynamic conditional correlation between sCDS and the domestic financial markets in Hungary and Sweden, as well as Kliber (2017).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…The others were sovereign bonds and the stock exchange markets. This study extends the research by Kliber (2016) who analysed changes in the dynamic conditional correlation between sCDS and the domestic financial markets in Hungary and Sweden, as well as Kliber (2017).…”
Section: Introductionsupporting
confidence: 68%
“…One can suspect that something happened then that changed the relationships between the markets, but the authors did not test any alternative international events. Kliber (2016) showed that such a change in relationships happened in Hungary and Sweden during the period between the announcement of the reform and the moment of its implementation, while the ISDA ( 2014) study shows that liquidity was dropping gradually from the announcement to the implementation. This is especially visible in the example of Hungary -the moment of change and the moment of implementation of domestic reforms took place at roughly the same time (see also : Orlowski and Tsibulina, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations